2011
DOI: 10.4166/kjg.2011.57.6.352
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Common Bile Duct Stone and Endoscopic Treatment after Endoscopic Papillary Large Balloon Dilatation with Minor Endoscopic Sphincterotomy

Abstract: Background/Aims: Recent studies have reported the potentials of endoscopic papillary large balloon dilatation (EPLBD) with minor endoscopic sphincterotomy (EST) for the complete removal of common bile duct (CBD) stone in the high risk groups. However, there have been no reports about the recurrence of the CBD stone after EPLBD with minor EST. The aim of this study was to evlauate the recurrence of CBD stone after EPLBD with minor EST. Methods: A total of 1,036 patients who underwent endoscopic treatment due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Descriptive assessment and study characteristics. Out of 413 citations generated by the initial literature search, nine clinical trials with 1295 patients were finally enrolled in the meta-analysis according to the screening criteria, including six nonrandomized studies 11,[22][23][24][25][26] and three RCTs 9,27,28 (Fig. 1, Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Descriptive assessment and study characteristics. Out of 413 citations generated by the initial literature search, nine clinical trials with 1295 patients were finally enrolled in the meta-analysis according to the screening criteria, including six nonrandomized studies 11,[22][23][24][25][26] and three RCTs 9,27,28 (Fig. 1, Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The quality of nonrandomized studies were evaluated by NOS. Four out of six studies (66.7%) were ranked at level 2 (0–5) and two studies (33.3%) at level 1 (6–9) …”
Section: Resultsmentioning
confidence: 99%
“…However, there is no report about the physiologic and anatomical changes of the sphincter after EPLBD. Recent retrospective studies reported that the recurrence rate of choledocholithiasis was similar between EPLBD with limited EST and EST alone groups 15,16. However, these studies have some pitfalls which underestimated the preventive efficacy of recurrent stones by EPLBD since they did not take it account the fact that the patients who underwent EPLBD were more likely to have larger stones which could affect the biliary stone recurrence rate 17,18.…”
Section: Introductionmentioning
confidence: 99%
“…However, for the recurrence of CBD stones, the role of EPLBD has not been established. Recently, it has been reported that more than 15 mm EPLBD prevented the short-term recurrence of CBD stones (7) while EPLBD (12 mm to 20 mm) reduced recurrence in patients with periampullary diverticula (8). Because large balloon dilation carries the risk of complications when the CBD is not adequately dilated or has a stricture, EPLBD should be performed cautiously, according to the CBD diameter.…”
Section: Introductionmentioning
confidence: 99%